2015
DOI: 10.2174/1381612821666150909094712
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-16-5p Controls Development of Osteoarthritis by Targeting SMAD3 in Chondrocytes

Abstract: MicroRNAs (miRNA), small noncoding RNA molecules, are endogenous regulators of gene expression that have been implicated in the pathogenesis of various diseases such as cancer and arthritis. The aim of this study was to explore the biological function of microRNA-16-5p (miR-16-5p) and the molecular mechanism in osteoarthritis (OA). MiRNA targets were identified using bioinformatics. Using real-time PCR, the expression of miR-16-5p and SMAD3 in cartilage specimens was determined in 10 patients with knee OA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 0 publications
5
43
0
Order By: Relevance
“…Three independent experiments were performed in each assay. Several studies had demonstrated that miRNAs played a vital role in the regulation of the OA development, including miR-210 (21), miR-16 (22), miR-21 (23), and miR-142 (24). This study found the up-regulation of miR-4262 in TNF-α-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 49%
“…Three independent experiments were performed in each assay. Several studies had demonstrated that miRNAs played a vital role in the regulation of the OA development, including miR-210 (21), miR-16 (22), miR-21 (23), and miR-142 (24). This study found the up-regulation of miR-4262 in TNF-α-treated chondrocytes.…”
Section: Discussionsupporting
confidence: 49%
“…Also knee and hip AC of OA patients exhibit increased miR-16 expression compared to healthy AC [151,152]. SMAD3 has been determined as a direct target of miR-16, implicating this miRNA in the switch to catabolic TGF-β signaling [152].…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…Also knee and hip AC of OA patients exhibit increased miR-16 expression compared to healthy AC [151,152]. SMAD3 has been determined as a direct target of miR-16, implicating this miRNA in the switch to catabolic TGF-β signaling [152]. Notably, FGF2 is a direct transcriptional target of miR-16 in human nasopharyngeal carcinoma cells [153], indicating additional repression of FGF2 signaling by this miRNA.…”
Section: Mirna Regulation Of Fibroblast Growth Factor 2 Transformmentioning
confidence: 99%
“…The cells were immunostained for collagen type II, as described in a previous study (18), prior to and after the experiments. Immunofluorescent images were gathered for each group using confocal laser scanning microscopy (LSM 710; Carl Zeiss AG, Oberkochen, Germany).…”
Section: Concentration Gradientmentioning
confidence: 99%